2022
DOI: 10.31004/basicedu.v6i2.2263
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Religious Character in Silat Tapak Suci in Students' Perspective

Abstract: This study aims to find moral, social and religious values as well as the environment in silat tapak suci. The research method used is descriptive qualitative. The selection of research subjects with purposive sampling technique. Data was collected using in-dept interview, observation and documentation techniques. The results showed that members are conducted some behaviour such as ablution activities, prayers, short lectures or cults, reading Al-Fatihah letters, and closing prayers and there was another advis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Internalization is a process in which individuals learn and are accepted as part of, and at the same time tie themselves into the values and social norms of the behavior of a society. (Bahagia et al, 2022;Bali & Rozhana, 2022;Istiyani & Wibowo, 2020). Based on this opinion, it can be concluded that internalization is a person's learning process so that someone can be accepted as part of society, then he bind himself to the values and social norms of his group's behavior in society.…”
Section: The Concept Of Internalizing the Values Of Monotheismmentioning
confidence: 98%
See 1 more Smart Citation
“…Internalization is a process in which individuals learn and are accepted as part of, and at the same time tie themselves into the values and social norms of the behavior of a society. (Bahagia et al, 2022;Bali & Rozhana, 2022;Istiyani & Wibowo, 2020). Based on this opinion, it can be concluded that internalization is a person's learning process so that someone can be accepted as part of society, then he bind himself to the values and social norms of his group's behavior in society.…”
Section: The Concept Of Internalizing the Values Of Monotheismmentioning
confidence: 98%
“…Unfortunately, moral decay is a condition that develops in society as well as an increasingly diversified governing environment. Crime, injustice, corruption, brutality against children, and violations of human rights are only a few examples (Ahmad et al, 2021;Bahagia et al, 2022). So, the implementation of Monotheistic Values is discussed in Surat Al-Fatihah Verse 5, four types of God's attributes are mentioned, namely: Educator of the whole world, Most Merciful, Most Compassionate, and One who controls the day of retribution.…”
Section: Introductionmentioning
confidence: 99%